Problems Of Ensuring Gender Equality (Progress Annals: Journal of Progressive Research, 2024)
"The issues of ensuring gender equality are one of the urgent directions of social policy in Uzbekistan. Although legal and institutional frameworks for the development of gender equality have been established in the country, certain challenges remain in practice. This article analyzes the existing problems in ensuring gender equality in Uzbekistan, particularly the protection of women's rights, the creation of equal opportunities in education and the labor market. Moreover, it examines ways to overcome social barriers stemming from gender stereotypes."